[X]uniqMAP: unique gene sequence regions in the human and mouse genomes - Jiménez, José L (BioMed Central, 2006)
BACKGROUND: Current approaches for genome-wise functional analyses, such as microarray and RNA interference studies, rely on the specificity of oligonucleotide sequences to selectively target cellular transcripts. The design of specific oligos involves the determination of unique DNA regions in the gene/transcripts of interest from the targeted organism. This process is tedious, time consuming and it does not scale up for high-throughput studies. DESCRIPTION: Taking advantage of the availability of complete genome sequence information for mouse and human, the most widely used systems for the study of mammalian genetics, we have built a database, [X]uniqMAP, that stores the precalculated unique regions for all transcripts of these two organisms. For each gene, the database discriminates between those unique regions that are shared by all transcripts and those exclusive to single transcripts. In addition, it also provides those unique regions that are shared between orthologous genes from the two organisms. The database is updated regularly to reflect changes in genome assemblies and gene builds. CONCLUSION: Over 85% of genes have unique regions at least 19 bases long, with the majority being unique over 60% of their lengths. 14482 human genes share exactly at least a unique region with mouse genes, though such regions are typically under 40 bases long. The full data are publicly accessible online both interactively and for download. They should facilitate (i) the design of probes, primers and siRNAs for both small- and large-scale projects; and (ii) the identification of regions for the design of oligos that could be re-used to target equivalent gene/transcripts from human and mouse.